Drivers' comfort boundaries in pedestrian crossings: A study in driver braking characteristics as a function of pedestrian walking speed. (June 2015) - Lubbe, Nils; Davidsson, Johan
Highlights: Collision avoidance activations must balance speed reduction and undesired activation. Brake onset for pedestrians approaching at 1 m/s and 2 m/s was measured in a driving simulator. For pedestrians crossing at 1 m/s, 90% of drivers braked before 2.6 s TTC. At 2 m/s, 90% of drivers braked before 2.2 s TTC. These values could be valuable in optimizing differentiation between desired and undesired system activation. Abstract: Systems informing or warning a driver of an imminent collision with a pedestrian or automatically initiating braking have been introduced to the car market. One of the major challenges is to balance system performance against the possibility of undesired system activation. The distinction between desired and undesired system activation can be based on driver discomfort. In this study driver discomfort can be inferred from brake onset, which refers to the start of brake pedal depression, as the most intuitive way for a driver to resolve a conflicting situation. The influences of pedestrian walking speed on brake onset and brake deceleration levels were investigated in Toyota Motor Corporation's high-fidelity driving simulator. One hundred and eight naive volunteers drove at a target speed of 30 km/h in an urban environment and were subjected to two animations of pedestrian crossing situations projected inside the driving simulator. The pedestrian speed was 1 m/s and 2 m/s. Time To Collision (TTC) at brake onset, one of the recorded quantities, might be a suitable measure for comfort zone boundaries as it is less affected by driving speed than other measures. Pedestrian speed was found to have a statistically significant influence on brake onset. For pedestrian speeds of 1 m/s, 90% of drivers braked before 2.6 s TTC. For 2 m/s this value was 2.2 s. These values can be used to differentiate between desired and undesired system activation in the design of an "unjustified system response" test in the assessment of pedestrian safety systems.